Exercise Intervention Promotes the Growth of Synapses and Regulates Neuroplasticity in Rats With Ischemic Stroke Through Exosomes - Li, Chen; Ke, Changkai; Su, Yue; Wan, Chunxiao (Frontiers in Neurology, 2021)
Background—Exercise produces neuroprotection by improving neuroplasticity. Exercise can induce exosome production. Exosomes are involved in repairing brain function, but the relationship of exercise, exosomes and neuroprotection have not been elucidated. This study intends to explore the relationship and potential mechanism by observing the changes in the exosome level, infarct volume, neurological function, synapses and corticospinal tract (CST). Methods—Rats were randomly divided into four groups: a sham operation (SHAM) group, middle cerebral artery occlusion (MCAO) with sedentary intervention (SED-MCAO) group, MCAO with exercise intervention (EX-MCAO) group, and MCAO with exercise intervention and exosome injection (EX-MCAO-EXO) group. The exercise intervention was started 1 d after MCAO and lasted for 4 w. The levels of exosomes in serum and brain, gait analysis and magnetic resonance scan were performed 1 w and 4 w after the intervention. After 4 w of intervention, the number of synapses and synaptophysin (Syn) expression were detected. Results— After 4 w of intervention, 1. The EX-MCAO and EX-MCAO-EXO groups showed higher serum exosome and brain exosome levels than the SED-MCAO group, of which the EX-MCAO group had the highest serum exosome and the EX-MCAO-EXO group had the highest brain exosome levels. 2. The number of synapses and the Syn expression in the EX-MCAO and EX-MCAO-EXO groups were significantly higher than that in the SED-MCAO group, among which the EX-MCAO-EXO group exhibited better. 3. Compared with the SED-MCAO group, the EX-MCAO and EX-MCAO-EXO groups had significantly improved infarct volume ratio, rFA value and rADC, of which the EX-MCAO-EXO groups displayed a greater improvement. 4. Compared with the SED-MCAO group, The EX-MCAO group and EX-MCAO-EXO group had significantly lower mNSS scores and improved gait. 5. The serum and brain exosome levels were negatively correlated with the mNSS score, infarct volume ratio and rADC value and positively correlated with the rFA value and Syn expression. The serum and brain exosome levels showed a strong positive correlation. Conclusions—Exercise intervention increases the serum exosome level, which are recruited into the brain, leading to improved synaptic growth and CST integrity, a reduced infarct volume, and improved neurological function and gait.